ANALISIS KINERJA KARYAWAN PERUSAHAAN TEXTILE PADA MASA PANDEMI - Risky Budi Setiawan; Hawik Ervina Indiworo Hawik; Ratih Hesty Utami P (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2021)
The ipurpose iof ithis istudy iwas ito idetermine ithe ieffect iof icompensation, iwork istress iand ileadership ion iemployee iretention idue ito ia idecrease iin iturnover iintention iat iPT. iApparel iOne iIndonesia iSewing iSection. iThe itype iof iresearch ithat iwill ibe iused iis iassociative iwith ia iquantitative iapproach. iThe ipopulation iin ithis istudy iwere iemployees iof ithe isewing isection iof iPT. iApparel iOne iIndonesia, itotaling i478 ipeople, iwhile ithe isample iused iin ithis istudy iwas i100 irespondents iusing ia inon-probability isampling itechnique iwith ipurposive isampling itype. iThe imethod iof idata icollection iis ithrough ithe idistribution iof iquestionnaires iwhile ithe ianalysis iused iin ithis istudy iis imultiple ilinear iregressio The iresults ishowed ithat ithe ivariable iinfluence iof icompensation, ijob istress iand ileadership ihad ia ipositive iand isignificant ieffect ion iturnover iintention iand ithe iresult iof ithe iadjusted iR isquare ivalue iin ithe iregression imodel iwas iobtained iat i0.785, iwhich imeans ithat i78.5 ipercent iof ithe ivariable iturnover iintention ican ibe iexplained iby ithe ivariables iof icompensation, iwork istress iand ileadership. iwhile ithe iremaining i21.5 ipercent iis iexplained iby iother ivariables ioutside iof ithis istudy.